A formação dos professores e os direitos humanos das crianças e dos adolescentes: uma pesquisa intercultural sobre a não-violência - Lemes, João Loredi (2022)
This Doctoral thesis work is a study about the biggest problems faced by Educators, who come from the involvement with children and adolescents who suffer abuse, whether in society, at school or in their own family. This project, based on the Line of Teaching Training, Knowledge, and Professional Development (Training, Knowledge and Professional Development - LP1 - PPGE - UFSM), is aimed for Teacher Training because I understand that the teaching activity must be reviewed to build or improve the pedagogical path. I believe that a research like this will help educators to reflect on the current social position and have a new view about their own students. This is, therefore, a critical reflection on the Human Rights of Children and Adolescents, analyzing this representation for the society of the interior of RS through the preservation of peace and the propagation of "Non-Violence". There is also an investigation regarding the assumptions of interculturality and its influence on contemporary pedagogical interactions, having as theoretical reference the work of the writer and researcher Humberto Maturana (MATURANA, 2011), based on his study on the Biology of Love. In possession of such reflections, I research on cultural differences to reduce inequality, contributing to the formation of increasingly humanizing teachers. Thus, I sought to act to better direct the teaching action, considering that teachers are the holders of a key role in this social field. The influence of such findings and their analysis will certainly contribute to the new teaching images and the continuous training of teachers, with an intercultural perspective and respect for the citizen.